Fabrication of janus type bi-layer polymeric membranes for advance water purification. (2021) - Chakraborty, Triparna; Kanth P., Chandra; Trivedi, Maitrayee U.; Tripathi, Brijesh; Pandey, Manoj Kumar
Abstract: Membrane technology plays a vital role in various applications like desalination, ultrafiltration, nano-filtration, reverse osmosis and wastewater treatment. Janus membranes (JMs) are a unique class of polymers having divergent hydrophilic/hydrophobic properties on both sides of their interface. JMs have been exclusively used in the fields of fluid flow to induce unidirectional fluid transportation at the required interfaces. Herein, we report the fabrication of two Janus type bi-layer polymeric membranes with hydrophilic and hydrophobic surfaces on opposite sides using a simple doctor blading method. First bi-layer Janus membrane consists of polyvinylidene fluoride (PVDF) coating on cellulose cotton fabric (CPV). Second bi-layer Janus membrane (NPV) consists of partly hydrophilic nylon 6, 10 top layer and hydrophobic PVDF bottom layer. PVDF and nylon 6, 10 solutions are cast of a suitable thickness over the respective bottom layers. Prepared Janus membranes were characterised by SEM, FTIR and UV–Visible spectroscopy. Water contact angle measurements confirmed the hydrophilic and hydrophobic behaviour on opposite sides of the membranes. Porosity and equilibrium water content measurements established that both Janus membranes retain native properties of their constituent polymers. These newly engineered Janus type polymeric membranes could find potential application in creating unidirectional fluid flow transfer such as oil–water separations.